Analisis Tabarruj Terhadap Profesi Model Muslimah: Studi Komparatif Ulama Klasik dan Ulama Kontemporer - Angraeni, Tri; Aisyah, Siti (Universitas Islam Negeri Alauddin Makassar, 2023)
The profession of a model requires discipline, commitment, responsibility and perseverance and totality. Some people think it's possible for a woman to wear a hijab to become a model and walk on the catwalk. While some people argue that women who wear hijab should not be models because it is against religious rules. The methodology used in this study uses a descriptive qualitative research type. The data sources use primary and secondary data sources where primary data uses the holy book of the Qur'an and hadith while secondary data uses literature such as books, journals, scientific works in the form of theses, theses. The results of this study indicate that the activities of the Muslim model profession which are included in tabarruj behavior include: catwalk models, photo models, and advertising models. In practice, the Muslim model shows the beauty of her body, wears a camel's hump bun, is excessively decorated, softens her voice, performs ikhtilat, and poses by revealing her curves. This activity is nothing but tabarruj behavior. The classical Ulama's view recommends that women should stay at home, except in an emergency/urgent situation, they are allowed to leave the house, but pay attention not to be excessively ornate. Meanwhile, the views of contemporary scholars have an attitude of tolerance, but that means there is no prohibition.